2002
DOI: 10.1021/bi0117551
|View full text |Cite
|
Sign up to set email alerts
|

Single Replacement Constructs of All Hydroxyl, Basic, and Acidic Amino Acids Identify New Function and Structure-Sensitive Regions of the Mitochondrial Phosphate Transport Protein

Abstract: The phosphate transport protein (PTP) catalyzes the proton cotransport of phosphate into the mitochondrial matrix. It functions as a homodimer, and thus residues of the phosphate and proton pores are somewhat scattered throughout the primary sequence. With 71 new single mutation per subunit PTPs, all its hydroxyl, basic, and acidic residues have now been replaced to identify these essential residues. We assayed the initial rate of pH gradient-dependent unidirectional phosphate transport activity and the liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Another possible site for proton coupling is the asymmetric H33. The equivalent residues in the ortholog ScMir1p are essential for function (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible site for proton coupling is the asymmetric H33. The equivalent residues in the ortholog ScMir1p are essential for function (18).…”
Section: Resultsmentioning
confidence: 99%
“…The mutations E95Q, K98A, E192Q, S195A, and K295A of the phosphate transporter ScMir1p (Fig. S10 in SI Appendix) reduced the transport activity to 72%, 3%, 39%, 3%, and 33% of the wild-type activity, showing that apolar substitutions render the transporter dysfunctional, whereas polar substitutions are less severe (18). Notably, mutations need not have a strong effect, because they may only change the transport mode from exchanger to uniporter or vice versa (see below).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphate carrier Mir1p has basic residues at contact points I and II that mutagenesis shows are important for its transport function (15). The binding site is similar to that of keto acid carriers, but a single phosphate anion is too small to be bound at contact points I and II simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of residue 182 BtAAC1 at contact point II affect carrier function in yeast Mir1p (15) and Ctp1p (18), human OGC (19) and UCP1 (20), and hamster mitochondrial folate transporter͞carrier (12). Hyperornithinemia-hyperammonia-homocitrullinuria syndrome is associated with the mutation E180K in ornithine transporter (ORNT) 1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this dilemma, the heterologous expression/reconstitution system, as discussed already, is indeed most helpful. Using this approach, a most detailed analysis has been carried out with the phosphate transporter (32). These studies led to likely phosphate and proton transport paths within the protein and identified two amino acids that may be central in the synchronization of these two pathways to yield the physiologically relevant electroneutral and proton-compensated phosphate transport (Figs.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%